(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to provide on overview and explanation of public service accountability in the process of building permit service in the Gowa Regency Investment and One Door Integrated Services Office. This study used qualitative research by using the type of phenomenology. The number of informants in this study was seven people. The results of this study showed that for the Government of Gowa Regency in order to create an excellent service system. From an academic point of view, the results were expected to be useful for the development of administrative science. The result of this study showed that the government of Gowa Regency had not been accountable for providing services reference not yet fully oriented towards the community in obtaining services. Therefore, it was necessary for the government to increase transparency and accountability in services, especially in service costs and the length of the service process that the community complained about.